COMPARISON OF THE RESULTS OF GLENOHUMERAL JOINT RADIOGRAPH IMAGES DESCRIPTION ON AP OBLIQUE WITH 15O, 25O, 30O, AND HORIZONTAL ANGULAR BEAM - Saleh Mursyid (Poltekkes Kemenkes Semarang, 2020)
Glenohumeral joint is the broadest joint in our body. Joint glenohumeral joints bullet includes joint with very shallow bowls. The examination technique to see the glenohumeral joint is with the AP position, RPO and LPO formed the Oblique patient position with 15o, 25o, 30o and horizontal angular beam. This comparison research to know the results of Glenohumeral Joint Radiograph Oblique images on AP with of 15o, 25o, 30o and angular horizontal beam at the Radiology Installation of Ulin Banjarmasin Hospital. This research is descriptive quantitative design. Data collected by observing, and based on the results of questionnaires that distributed to 20 respondents to see the results of comparison Glenohumeral Joint Radiograph on AP Oblique images with of 15o, 25o, 30o and angular horizontal beam at the Radiology Installation of Ulin Banjarmasin Hospital. Using a horizontal beam angular direction is better Because The joint gap between the head of the humerus and the glenoid fossa is completely open and there is a very clear images of the glenoid fossa. There are differences in the Joint Glenohumeral on AP Oblique radiographs with 15o, 25o, 30o and horizontal angular beam.